Assessment of the effect of changes in consolidation conditions in the advance of the carbonation front in cementitious matrix composites - Silva,Ruan Gustavo Rezende (2021)
ABSTRACT: Carbonation is one of the main deleterious effects of reinforced concrete structures, as it creates a favorable condition for the reinforcement depassivation and, thus, facilitates the onset of the corrosive process. The phenomenon is directly influenced by the material void’s structure, which is affected by the consolidation of the mass in the fresh state, subject evaluated in this study. For this purpose, samples were made using two water to cement ratios and defining two different consolidation methods. Compressive strength tests were carried out for the mechanical characterization of the specimens, in addition to accelerated carbonation tests, monitoring the progress of the carbonated thickness using the phenolphthalein colorimetric indicator, during 98 days. Microstructural differences were evaluated by scanning electron microscopy (SEM). The results indicate that the lower the workability of the mixture, the greater the impacts on the compressive strength of the material, resulting from failures in the consolidation stage. Nevertheless, another behavior is observed when evaluating this effect in the advancement of the carbonation front, indicating that the voids structure of the material should not be evaluated only according to its volume, but also in terms of the pattern of its distribution, its morphology and its connectivity.